Synthesis of renewable high-density fuel with isophorone - Wei Wang (Nature Portfolio, 2017)
Abstract 1,1,3-Trimethyl-5-(2,4,4-trimethylcyclohexyl)cyclohexane, a renewable high density fuel, was first produced in a high overall carbon yield (~70%) with isophorone which can be derived from hemicellulose. The synthetic route used this work contains three steps. In the first step, 3,3,5-trimethylcyclohexanone was synthesized by the selective hydrogenation of isophorone. Among the investigated catalysts, the Pd/C exhibited the highest activity and selectivity. Over this catalyst, a high carbon yield (99.0%) of 3,3,5-trimethylcyclohexanone was achieved under mild conditions (298 K, 2 MPa H2, 1 h). In the second step, 3,5,5-trimethyl-2-(3,3,5-trimethylcyclohexylidene)cyclohexanone was produced in a high carbon yield (76.4%) by the NaOH catalyzed self-aldol condensation of 3,3,5-trimethylcyclohexanone which was carried out in a round bottom flask attached to the Dean–Stark apparatus. In the third step, the 3,5,5-trimethyl-2-(3,3,5-trimethylcyclohexylidene)cyclohexanone was hydrodeoxygenated under solvent-free conditions. High carbon yield (93.4%) of 1,1,3-trimethyl-5-(2,4,4-trimethylcyclohexyl)cyclohexane was obtained over the Ni/SiO2 catalyst. The 1,1,3-trimethyl-5-(2,4,4-trimethylcyclohexyl)cyclohexane as obtained has a density of 0.858 g mL−1 and a freezing point of 222.2 K. As a potential application, it can be blended into conventional fuels (such as RP-1, RG-1, etc.) for rocket propulsion.